2020
DOI: 10.3390/photonics7040098
|View full text |Cite
|
Sign up to set email alerts
|

Estimations of Low-Inertia Cubic Nonlinearity Featured by Electro-Optical Crystals in the THz Range

Abstract: Despite the growing interest in nonlinear devices and components for light by light control in the terahertz range, there is a shortage of such materials and media used for these purposes. Here, we present the calculated values of low-inertia nonlinear refractive index coefficient for electro-optical crystals used in THz time-domain spectroscopy systems such as ZnSe, ZnTe, CdTe, GaP, and LiNbO3. The medium parameters affecting the cubic nonlinearity of the vibrational nature increase in the range of 0.5–1 THz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
(24 reference statements)
2
7
0
Order By: Relevance
“…The value is very close to the measurement result obtained by the authors of cm /W 27 . Note that in work 15 the theoretical estimate of this coefficient was cm /W, which is in good good agreement with our measurement results. The difference in exact value is due to the assumptions and approximations of our theoretical model.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The value is very close to the measurement result obtained by the authors of cm /W 27 . Note that in work 15 the theoretical estimate of this coefficient was cm /W, which is in good good agreement with our measurement results. The difference in exact value is due to the assumptions and approximations of our theoretical model.…”
Section: Resultssupporting
confidence: 91%
“…This can be explained by the fact that in the THz range the value of nonlinear refractive index significantly exceeds the value for the visible and IR frequency ranges 16 . For lithium niobate, this excess is 4 orders of magnitude 15 .…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24] Intense THz can be used to perform nonlinear experiments and unveil the transient couplings of the different HB modes. [25][26][27][28][29][30][31][32][33][34] The first results detailing the nonlinear response of water in the THz frequency range are recent, 27,28,32,33,35 and the molecular interpretation is still a matter of ongoing discussion. Tcypkin et al 32,33 performed a series of z-scan measurements at B1 THz on liquid water and associated the third-order nonlinear signal to cascaded second-order anharmonicity of the intramolecular O-H stretching modes.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the fact that in the THz range, the value of nonlinear refractive index n 2 significantly exceeds the value for the visible and IR frequency ranges 16 . For lithium niobate, this excess is 4 orders of magnitude 15 .…”
Section: Analytical Resultsmentioning
confidence: 99%
“…Recently, it has been theoretically predicted and experimentally confirmed that the coefficient of the nonlinear refractive index of materials in the terahertz frequency range can be several orders of magnitude higher than its value for the same materials in the visible and near-IR spectral ranges [14][15][16] . This nonlinearity has low-inertia mechanism, which means that high-speed THz photonics devices based on nonlinear effects are promising.…”
Section: Introductionmentioning
confidence: 99%